Integrated care for older people based on information and communication technology: a scoping review protocol. Issue 7 (21st July 2022) - Tian, Yutong; Zhang, Yan; Wang, Shanshan; Cheng, Qingyun; Meng, Lixue
Abstract : Introduction: Integrated care is an effective means of coping with the increasingly complex healthcare needs of elderly and alleviating pressure on national pension services. WHO regards integrated care as a method of providing high-quality healthcare and advocates integrated care based on digital technology. Against the backdrop of the COVID-19 pandemic, information and communication technology (ICT) has become a facilitator for the successful implementation of integrated care by providing a platform for information sharing, team communication and resource integration. This scoping review aims to assess internationally published evidence concerning experiences and practice of ICT-based implementation of integrated care for older people. Methods and analysis: The study will follow the research framework developed by Arksey and O'Malley for scoping reviews. We will conduct a systematic search of the literature published from January 2000 to March 2022 via electronic databases, grey literature databases, websites of key organisations and project funding sources, key journals and reference lists included in selected papers, employ the Joanna Briggs Institute Literature Quality Assessment Tool to assess the quality of the included literature and apply thematic analysis to sort and summarise the content of the included studies. This study will begin in March 2022 and will be completed in December 2022. Ethics and dissemination: Ethical approval for this scoping review was granted by the Academic Committee of Zhengzhou University (ZZUIRB2021-155). This study will summarise the modes of operation and effects, barriers and facilitators of ICT-based implementation of integrated care for older people. We propose to recruit older people and integrated care service providers in rural primary healthcare centres and use a structured process of concept mapping to consult and discuss the results of our scoping review to construct an integrated care model and service pathway for older adults that is appropriate to the Chinese social context.